Microscale Toxicity Identification Evaluation (TIE) for interstitial water of estuarine sediments affected by multiple sources of pollution - Alves, Aline Vecchio; Ferraz, Mariana Aliceda; Moreno, Beatriz Barbosa; Nobre, Caio Rodrigues [UNESP]; Antunes, Renata Medeiros; Pusceddu, Fabio Hermes; Bordon, Isabella Cristina da Costa Leal; Favaro, Deborah Inês Teixeira; Cotrim, Marycel Elena Barbosa; Choueri, Rodrigo Brasil (Springer Nature, 2022)
Estuaries in the world are affected by different contamination sources related to urbanisation and port/industrial activities. Identifying the substances responsible for the environmental toxicity in estuaries is challenging due to the multitude of stressors, both natural and anthropogenic. The Toxicity Identification and Evaluation (TIE) is a suitable way of determining causes of toxicity of sediments, but it poses difficulties since its application is labour intensive and time consuming. The aim of this study is to evaluate the diagnosis provided by a TIE based on microscale embryotoxicity tests with interstitial water (IW) to identify toxicants in estuarine sediments affected by multiple stressors. TIE showed toxicity due to different combinations of metals, apolar organic compounds, ammonia and sulphides, depending on the contamination source closest to the sampling station. The microscale TIE was able to discern different toxicants on sites subject to different contamination sources. There is good agreement between the results indicated in the TIE and the chemical analyses in whole sediment, although there are some disagreements, either due to the sensitivity of the test used, or due to the particularities of the use of interstitial water to assess the sediment toxicity. The improvement of TIE methods focused on identifying toxicants in multiple-stressed estuarine areas are crucial to discern contamination sources and subsidise management strategies.
Keywords: Contamination; Ecotoxicology; Effect-directed analysis; Embryo-larval development; Pollution; Porewater; Toxicity identification and evaluation; Toxicity test